2-2(-3a-8)=6(a+4)

Simple and best practice solution for 2-2(-3a-8)=6(a+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-2(-3a-8)=6(a+4) equation:


Simplifying
2 + -2(-3a + -8) = 6(a + 4)

Reorder the terms:
2 + -2(-8 + -3a) = 6(a + 4)
2 + (-8 * -2 + -3a * -2) = 6(a + 4)
2 + (16 + 6a) = 6(a + 4)

Combine like terms: 2 + 16 = 18
18 + 6a = 6(a + 4)

Reorder the terms:
18 + 6a = 6(4 + a)
18 + 6a = (4 * 6 + a * 6)
18 + 6a = (24 + 6a)

Add '-6a' to each side of the equation.
18 + 6a + -6a = 24 + 6a + -6a

Combine like terms: 6a + -6a = 0
18 + 0 = 24 + 6a + -6a
18 = 24 + 6a + -6a

Combine like terms: 6a + -6a = 0
18 = 24 + 0
18 = 24

Solving
18 = 24

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -4a+2=-8a-14 | | x^2+11x+18= | | -15a-5=14a+10 | | p-7*4= | | x^2+11+18= | | -14x=-98 | | 3z=6z+12 | | -5s+7=-4s+12 | | 3x+11=5x-9 | | 4(2x-6)=56 | | -1+4x=3x+3 | | -8.1x-2.1=-1.6x+7.26 | | 7x=-70 | | 4x=40 | | 3x+3=4x-4 | | X^4+1=2X^2 | | 19=5x-7 | | 5x+4y=-16 | | 50x=130x | | 35=14x+5 | | 9x+15=6x+15 | | 2x+15=x+15 | | -26=4+5x | | 80=11x-10 | | 3X^2+33X+72=0 | | 4M^2-20M=0 | | -13x=52 | | T^2=5T | | 8x-2=38 | | 4M^2-20M+25=0 | | 2(4x+3)=8x-3(x+3) | | 2X+28=12X-62 |

Equations solver categories